Evaluation of quantity-intensity relationships of potassium in deeply weathered soil profile developed over granite from Peninsular Malaysia - Hamdan, J.; Burnham, C.P.; Ruhana, B. (Marcel Dekker Inc., 1999)
The potassium (K) supplying capacity of a deeply weathered profile developed over granite from Peninsular Malaysia was investigated by employing the quantity-intensity (Q/I) approach. The values of potential buffering capacity (PBC(K)), labile K (K(L)), specific K (K0), and specific K sites (K(X)) were considerably higher in the saprolite zones as compared to the solum layers. This indicated that depletion of K on cropping would be faster in the solum materials than in the saprolites. Potassium equilibrium activity ratio was in the sequence: solum > middle saprolite > upper saprolite. Free energy values showed low, but sufficient, level of available K reserve in this profile. The relationships of Q/I parameters with physico-chemical characteristics and clay mineralogy of the profile were discussed. The changes in the Q/I parameters as a function of depth were found to be associated with the contents of clay and organic matter in the solum, while in the saprolites, the clay mineralogy which composed mainly of K-feldspar, mica, and mica-smectite seemed to be the main factor.